The Recent Evolution of Early-Type Galaxies as Seen in their Cold Gas. Issue Volume 10:Issue S309(2014) (9th February 2015) - Young, Lisa M.
Abstract: I present an overview of new observations of atomic and molecular gas in early-type galaxies, focusing on the Atlas 3D project. Our data on stellar kinematics, age and metallicity, and ionized gas kinematics allow us to place the cold gas into the broader context of early-type galaxy assembly and star formation history. The cold gas data also provide valuable constraints for numerical simulations of early-type galaxies.